Model Pembelajaran Project-Based Learning (PjBL) melalui Video Project dalam Meningkatkan Kreativitas dan Keterampilan Peserta Didik - Nusfiyah, Khuzrotun (Journal of Islamic Education, 2024)
The aim of this research is to describe the use of learning methods using the Project Based Learning (PjBl) approach in the theme of learning procedure texts in class XI Indonesian language subjects at Sunan Drajat Lamongan Vocational School. This field research method involved 15 students who were members of 5 groups. Each group is required to make a project in the form of a video with a procedural text theme. The research results showed that learning using the Project Based Learning (PjBl) method was able to increase students' creativity and skills in learning. It becomes easier for students to understand and apply when compiling procedural texts